Towards the development of adaptation options using climate and crop yield forecasting at seasonal to multi-decadal timescales - Challinor, Andrew J. (Elsevier, 2009)
In order for climate forecasting to be used in developing adaptation options, the forecasts should be able to affect decisions made by stakeholders in a manner that improves outcomes. The implications of this requirement for forecasting are presented under five headings: relevance, reliability, stakeholder engagement, holism and accuracy. These characteristics are elucidated through a particular focus on the use of ensemble climate and crop simulations. Resulting recommendations, including comments on mainstreaming and seamlessness, are described using the concepts of quality and value.